School Furniture and Musculoskeletal Disorders in Left-Handed Students - Nurul Retno Nurwulan; Adhelia Bella Kristiani (KESMAS UWIGAMA: Jurnal Kesehatan Masyarakat, 2020)
Background: Left-handed students face difficulties in the classroom since the furniture are designed for the right-handed population. Left-handed students are forced to adjust their posture in order to reach the table on the right side of the chair. This awkward posture may cause musculoskeletal disorders (MSDs) in left-handed students. Objectives: This study aimed to evaluate the impact of existing school furniture on the risk of MSDs in left-handed students. We also evaluated the potential benefit of the appropriate chair for left-handed students in reducing musculoskeletal discomforts. Research Methods: A total of 14 left-handed students were given the Nordic Musculoskeletal Questionnaires (NMQ) to identify their health problems related to school furniture. The deviation degree of neck and lower back from the upright sitting posture was used to evaluate the impact of the appropriate chair. Results: Pearson’s correlation showed that prolonged sitting, awkward posture, and class duration are related to the musculoskeletal discomforts. From the paired t-test evaluation, it is evident that the appropriate chair for left-handed students could reduce the deviation degree of neck and lower back from the upright sitting posture. Conclusion: The improper school furniture increases the risk of MSDs in left-handed students. A chair that could accommodate both the right-handed and left-handed students is important to reduce the risk of MSDs in students. Keywords: Left-handed; awkward postures; NMQ; musculoskeletal disorder.